Influence of date of transplanting on the growth and yield performance of high yielding varieties of Boro rice: Yield of Boro rice as affected by transplanting date (Journal of the Bangladesh Agricultural University, 2019)
An experiment was conducted to find out the effect of variety, date of transplanting and its interaction on the growth and yield performance of high yielding Boro rice. The experiment comprised five varieties viz., BRRI dhan28, BRRI dhan58, BRRI dhan67, BRRI dhan69, BRRI dhan74 and five dates of transplanting viz., 15 December, 30 December, 15 January, 30 January and 15 February. The experiment was laid out in a randomized complete block design with three replications. Results revealed that growth parameters, crop characters, yield components and yield were significantly influenced by variety, date of transplanting and their interactions. The leaf area index (LAI) and dry matter production hill-1 were highest in BRRI dhan69 when transplanted on 15 January whereas the lowest value was found in BRRI dhan28 when transplanted on 15 February. The number of effective tillers hill-1 (11.80), number of grains panicle-1 (130.90), 1000-grain weight (22.07 g), grain yield (4.96 t ha-1) and straw yield (6.64 t ha-1) were highest in BRRI dhan69 whereas corresponding lowest values were recorded in BRRI dhan28. The crop transplanted on 15 January produced the highest number of effective tillers hill-1 (12.81), highest number of grains panicle-1 (131.20), heaviest 1000-grain weight (21.93 g), highest grain yield (5.36 t ha-1) and highest straw yield (7.71 t ha-1). In case of interaction, the highest grain (5.90 t ha-1) and straw yields (7.87 t ha-1) were recorded in BRRI dhan69 transplanted on 15 January whereas the lowest grain and straw yields were recorded in BRRI dhan28 transplanted on 15 February. Therefore, it can be concluded that BRRI dhan69 along with 15 January transplanting appears as the promising combination in terms of grain and straw yields.J Bangladesh Agril Univ 17(3): 301–308, 2019